2022
DOI: 10.3390/cells11172659
|View full text |Cite
|
Sign up to set email alerts
|

Ependymal and Neural Stem Cells of Adult Molly Fish (Poecilia sphenops, Valenciennes, 1846) Brain: Histomorphometry, Immunohistochemical, and Ultrastructural Studies

Abstract: This study was conducted on 16 adult specimens of molly fish (Poecilia sphenops) to investigate ependymal cells (ECs) and their role in neurogenesis using ultrastructural examination and immunohistochemistry. The ECs lined the ventral and lateral surfaces of the optic ventricle and their processes extended through the tectal laminae and ended at the surface of the tectum as a subpial end-foot. Two cell types of ECs were identified: cuboidal non-ciliated (5.68 ± 0.84/100 μm2) and columnar ciliated (EC3.22 ± 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 107 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Our previous study revealed the expression of S100 protein in the ependymal cells of Molly fish (Mokhtar, Sayed, et al, 2022). It has been reported that S100 protein is required for the defense systems by many species.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Our previous study revealed the expression of S100 protein in the ependymal cells of Molly fish (Mokhtar, Sayed, et al, 2022). It has been reported that S100 protein is required for the defense systems by many species.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the pancreatic acinar cell of intrahepatic pancreas and disseminated pancreas showed immunoreactivity to IL‐1β, NF‐κB, and Nrf2. Our previous studies reported the expression of these proteins in the intestinal bulb, spleen, liver, and ependymal cells of the Molly fish (Hussein et al, 2023, Mokhtar, Hussein, & Sayed, 2022, Mokhtar, Sayed, et al, 2022, Sayed et al, 2022). IL‐1β performs a variety of physiological functions, and fish retain its ability to use IL‐1β to regulate inflammatory process (Secombes et al, 2011), as it has a pivotal role in the local and systemic responses initiation to different stimuli through T and B lymphocytes, natural killer cells, and activating macrophages (Dinarello, 2011).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the areal distribution of this species seems to be related to the movements of different aquatic masses within the water column [ 54 ]. Despite some cases of pathogenic infections that have been recorded in Lampriformes [ 57 , 67 ], no information in these species about the immune system and its role in organism defense is available [ 68 , 69 , 70 ].…”
Section: Biological and Ecological Features Of Lampriformesmentioning
confidence: 99%